Instructional materials for educable mentally retarded children - Fianza, Minnie Lydia (1968)
The purpose of the study is to provide examples of instructional materials for the educable mentally retarded children who are to work alone, that is, while the teacher is directly working with a group in the same class. Instructional materials should have something to do with: intellectual development, imaginative and creative expression, social, emotional, manipulative, and motor development and self-help.